Micro clonal Reproduction of Ornamental Plants - Akbarova Muhayyo Xusanovna; Xomidova Marxaboxon Murodjon qizi (Genius Journals, 2022)
This article covers information on obtaining large quantities, high-quality, genetically identical, virus-free planting material using microglonal reproduction of orchid varieties from ornamental plants.
Keywords: clonal microcontroller, callus, tissue culture, regenerative plant, in vitro, apical meristema, explant, adventitious Bud